Legal Protection For Heirs Against Inheritance - Ramadhan, Fadel; Tjoanda, Merry; Latupono, Barzah (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: The agreement of all heirs to the transfer of land rights through sale and purchase is an important component that must be a concern for the parties who carry out the sale and purchase, especially inherited land. In this case, the holder of his land rights gets legal protection later, therefore, analyzing and reviewing the issue of legal protection to heirs of inherited property.Purposes of the Research: This study aims to find out how the validity of buying and selling inheritance without the knowledge of heirs and how legal protection to heirs against buying and selling inheritance property.Methods of the Research: This research uses normative juridical research methods, legal approaches, case approaches, conceptual approaches used in this research. In addition, to solve legal issues, sources of legal materials are needed, namely primair legal materials, secondary legal materials, and tertiary legal materials.Results Main Findings of the Research: Shows that the validity of the sale and purchase of inheritance assets of the Supreme Court of the Republic of Indonesia Decision Number 702 PK / PDT / 2020 which does not meet Article 1320 of the Civil Code and Article 1471 of the Civil Code. Furthermore, legal protection to heirs against the sale and purchase of inheritance can make new legal remedies with a deliberative approach to obtain a share of absolute rights or legitime portie in claiming losses that have been suffered by heirs based on the provisions of Article 913 of the Civil Code, if deliberation is unsuccessful, they can file a lawsuit based on Article 834 of the Civil Code and Article 835 of the Civil Code and Article 1365 of the Civil Code which is the basis for The context of legal protection to heirs which is the right and interest of heirs to the sale and purchase of an inheritance object.